Shaping physiological indices, swimming technique, and their influence on 200m breaststroke race in young swimmers - Strzala, M.; Stanula, A.; Glab, G.; Glodzik, J.; Ostrowski, A.; Kaca, M.; Nosiadek, L. (Journal of Sports Science & Medicine, 2015)
The aim of this study was to investigate somatic properties and physiological capacity, and analyze kinematic parameters in the 200 m breaststroke swimming race. Twenty-seven male swimmers participated in the study. They were 15.7±1.98 years old. Their average height was 1.80 ± 0.02 m and lean body mass (LBM) was 62.45 ± 8.29 kg. Physiological exercise capacity was measured in two separate 90 sec. all-out tests, one for the arms and second for legs. During the tests total work of arm cranking (TWAR) and cycling (TWLG) as well as peak of VO2 for arm (VO2peakAR) and leg (VO2peakLG) were measured. The underwater swimmers body movements were recorded during the all-out swimming 200m breaststroke speed test using an underwater camera installed on a portable trolley. The swimming kinematic parameters and propulsive or non-propulsive movement phases of the arms and legs as well as average speed (V200), surface speed (V200surface) and swimming speed in turn zones (V200turns) were extracted. V200surface was significantly related to the percentage of leg propulsion and was shown to have large effect on VO2peakLG in the Cohen analysis. V200turns depended significantly on the indicators of physiological performance and body structure: TWAR, VO2peak LG and LBM, LBM, which in turn strongly determined the measured results of TWAR, TWLG, VO2peakAR and VO2peakLG. The V200turns and V200surface were strongly associated with V200, 0.92, p < 0.001 and 0.91, p < 0.001 respectively. In each lap of the 200m swimming there was an increased percentage of propulsion of limb movement observed simultaneously with a reduction in the gliding phase in the breaststroke cycles.